Pemberdayaan Masyarakat Melalui Pengembangan Usaha Kuliner Dalam Meningkatkan Pendapatan Asli Daerah Di Kecamatan Parigi Tengah - Awaludin; Supriadi, Ali; Guasmin; yusuf, Dikcy; Rukhayati (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2026)
The development of culinary businesses based on Micro, Small, and Medium Enterprises (MSMEs) plays a strategic role in improving community welfare and contributing to Regional Original Income (PAD). This community service activity was conducted in the Sail Tomini area, Parigi Tengah District, Parigi Moutong Regency, Central Sulawesi Province, involving 30 participants from six villages. The objective of this activity was to identify culinary product types, packaging styles, and sales revenues, as well as to encourage the empowerment of entrepreneurs through the use of local raw materials. The methods used included site surveys, outreach, outreach, training, and mentoring. The results of the activity indicated that the community had developed various culinary businesses, such as yellow rice (nasi kuning), food stalls, various fried foods, meatballs, gado-gado (traditional Indonesian salad), beverages, and processed products such as chips and traditional cakes, reflecting the local economic potential. However, entrepreneurs still face challenges in business management, packaging innovation, and marketing strategies. Through training and mentoring, participants' knowledge and skills in business management, including financial record keeping, pricing, and social media utilization, improved. This activity has a positive impact on community empowerment and has the potential to increase income and contribute to local revenue (PAD) in Parigi Tengah District.